Research Progress on the Drug Resistance of ALK Kinase Inhibitors - Li, Zhen; Liu, Fang; Wu, Shuang; Ding, Shi; Chen, Ye; Liu, Ju (Current Medicinal Chemistry, 2022)
Background: The fusion and rearrangement of the ALK gene of anaplastic lymphoma kinase is an important cause of a variety of cancers, including non-small cell lung cancer (NSCLC) and anaplastic large cell lymphoma (ALCL). Since crizotinib first came out, many ALK inhibitors have come out one after another, but the fatal flaw in each generation of ALK inhibitors is the body's resistance to drugs. Therefore, how to solve the problem of drug resistance has become an important bottleneck in the application and development of ALK inhibitors. This article briefly introduces the drug resistance of ALK inhibitors and the modified forms of ALK inhibitors, which provide a theoretical basis for solving the drug resistance of ALK inhibitors and the development of a new generation of ALK kinase inhibitors. Methods: We use relevant databases to query relevant literature, and then screen and select based on the relevance and cutting edge of the content. We then summarize and analyze appropriate articles, integrate and classify relevant studies, and finally write articles based on topics. Results: This article starts with the problem of ALK resistance, first introduces the composition of ALK kinase, and then introduces the problem of resistance of ALK kinase inhibitors. Later, the structural modification to overcome ALK resistance was introduced, and finally, the method to overcome ALK resistance was introduced. Conclusion: This article summarizes the resistance pathways of ALK kinase inhibitors, and integrates the efforts made to overcome the structural modification of ALK resistance problems, and hopes to provide some inspiration for the development of the next generation of ALK kinase inhibitors.
Keywords: Non-small cell lung cancer